PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PLAYTOPIA KOTA JAKARTA BARAT - Putri Aisyah, Risda; Mardiana Yulianti, R.R. (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of leadership style and work discipline on employee performance, both partially and simultaneously at PT ABC, West Jakarta City. This type of research uses associative quantitative methods. The sampling technique used a saturated sample of 57 respondents. Data analysis techniques use data instrument tests, classical assumption tests. Quantitative data analysis techniques use simple linear regression, multiple linear regression, correlation coefficient, correlation of determination. Hypothesis testing using the t test and F test. The results of the analysis show: Leadership style partially has a positive effect on employee performance with a simple linear regression equation Y = 15.880 + 0.601 .6% means that performance is influenced by compensation by 46.6%. This is proven by the t test, which shows that the t value > t table (7.057 > 1.673) is confirmed by the p value < Sig.0.05 or significance < 0.05 (0.001 < 0.05). Work discipline partially has a positive effect on employee performance, shown by the simple linear regression equation Y = 5.159 + 0.834 68.3%. This is proven by the t test, the t value obtained > t table (11.021 > 1.673) and strengthened by the p value < Sig.0.05 or significance value < 0.05 (0.000 < 0.05). The research results of leadership style and work discipline simultaneously have a positive effect on employee performance, shown by the multiple linear regression equation Y = 4.945 + 0.131 X1 + 0.720 X2. The correlation coefficient value is 0.836, meaning it has a very strong level of relationship and the coefficient of determination is 68.7%, meaning that performance is influenced by compensation and work discipline by 68.7%, while the remaining 31.3% is influenced by other factors not researched. This is proven by the hypothesis test results obtained by the value Fcount > Ftable (62.458 > 4.02) and reinforced by the significance value < 0.05 (0.000 < 0.05). Thus it is proven that Ho is rejected and Ha is accepted.